Coal-based carbonaceous adsorbent for enriching coal bed gas as well as preparation method and use method of coal-based carbonaceous adsorbent

By preparing coal-based carbonaceous adsorbent, the problem of separation of CH4 and N2 in coalbed methane is solved, efficient purification and enrichment of coalbed methane is achieved, the utilization value of low-order coal is expanded, and the adsorption performance and environmental protection are improved.

CN119186490APending Publication Date: 2024-12-27SHANXI COKING COAL GROUP CO LTD COKING COAL CLEAN UTILIZATION LABORATORY BRANCH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410982898.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There is a lack of effective adsorbents in the prior art for purifying and enriching coalbed methane, especially when separating CH4 and N2, resulting in a decrease in CH4 combustion efficiency.

Method used

Low-order coal is used as raw material to prepare coal-based carbonaceous adsorbents by hydrothermal reaction with potassium hydroxide or sodium hydroxide solution and carbonization treatment. High-temperature carbonation and chemical activation are used to prepare coal-based carbonaceous with excellent adsorption properties. Adsorbent.

Benefits of technology

It realizes efficient separation of CH4 and N2 in coalbed methane, improves methane enrichment effect, broadens the utilization channels of low-end coal, and has environmentally friendly preparation process, cheap raw materials, and has high adsorption selectivity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186490A_ABST
    Figure CN119186490A_ABST
Patent Text Reader

Abstract

The invention aims to provide a coal-based carbonaceous adsorbent for adsorbing, purifying and enriching coal bed gas, a preparation method of the coal-based carbonaceous adsorbent and a use method for enriching the coal bed gas by using the coal-based carbonaceous adsorbent. The preparation method comprises the following steps: mixing coal with a potassium hydroxide or sodium hydroxide solution with a certain concentration, then carrying out hydrothermal reaction on the mixed solution at the temperature of 60-80 DEG C, standing after the reaction is finished, cooling to room temperature, and adjusting the pH value by using diluted hydrochloric acid; drying the product to obtain a precursor of the coal-based carbonaceous adsorbent; and transferring the precursor into a tubular furnace, carbonizing in an inert atmosphere at a high temperature of 600-800 DEG C, cooling to room temperature after carbonization is finished, taking out a solid material, and carrying out acid pickling, filtering and drying to obtain the coal-based carbonaceous adsorbent. The coal-based carbonaceous adsorbent obtained by the invention has relatively high adsorption capacity and excellent adsorption selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas separation and purification, and in particular to a coal-based carbonaceous adsorbent for adsorbing, purifying and enriching coalbed methane, a method for preparing the coal-based carbonaceous adsorbent, and a method for using the coal-based carbonaceous adsorbent to enrich coalbed methane. Background Art

[0002] Adsorption separation is based on the difference in the adsorption capacity of adsorbents for different components. By changing the pressure or temperature, specific components are selectively separated to achieve the purpose of separating mixed gases and purifying single-component gases. Adsorption separation has the advantages of easy adsorbent regeneration, low energy consumption, simple process operation, and easy to achieve high separation factors. It is a high-efficiency, low-energy separation method. The selection of adsorbents and the performance of adsorbents are crucial to the efficiency of the separation process. According to the adsorbent regeneration method, the corresponding cyclic adsorption processes are mainly temperature swing adsorption (TSA), pressure swing adsorption (PSA), vacuum adsorption (VSA), inert gas purification cycle, etc. The development of high-efficiency adsorbents is a prerequisite for the widespread application of adsorption separation technology. In-depth design and research on high-efficiency adsorbents will help further optimize the process route and thus develop more competitive adsorption separation technology.

[0003] Coalbed methane is an unconventional natural gas stored in underground coal seams, and its main component is CH4. In recent years, the rapid development of unconventional natural gas represented by low-concentration coalbed methane (extracted coalbed methane), low-saturation natural gas and shale gas has attracted worldwide attention. These unconventional natural gases can be used as an effective supplement to natural gas, effectively alleviating my country's dependence on foreign natural gas. However, a large amount of impurity gases such as nitrogen will be mixed in during the natural gas extraction process, among which the presence of CO2 and N2 will significantly reduce the combustion efficiency of CH4. Therefore, it is particularly important to achieve the effective enrichment of methane in low-concentration coalbed methane.

[0004] The carbon material adsorbents that are currently widely used are basically made of biomass materials. For example, CN 116116389 A provides a method for preparing a carbon-based adsorbent material for selective adsorption and separation of low-carbon hydrocarbons, using chitosan as a raw material through hydrothermal reaction and high-temperature carbonization reaction to prepare an ultra-microporous carbon material adsorbent. This carbon-based adsorbent can meet the requirements of high-selectivity screening and separation of ethylene / ethane and propylene / propane, but does not meet the requirements of CH4 / N2 separation in unconventional natural gas.

[0005] For another example, CN 112830490A provides a carbon material adsorbent for adsorbing CO2. It uses water-soluble vitamins niacin and folic acid as carbon sources, obtains unactivated vitamin-based carbon material after high-temperature carbonization under inert gas, soaks the unactivated vitamin-based carbon material in an alkaline solution, and activates it again at 600°C-800°C for 1-3h to obtain a carbon material adsorbent with a high CO2 adsorption capacity and applies it to the application field of CO2 adsorption.

[0006] There are few adsorbents for purifying and enriching coalbed methane in the prior art. The present invention attempts to provide a coal-based carbonaceous adsorbent for adsorbing, purifying and enriching coalbed methane, a method for preparing the coal-based carbonaceous adsorbent, and a method for using the coal-based carbonaceous adsorbent to enrich coalbed methane. Summary of the invention

[0007] The present invention attempts to provide a coal-based carbonaceous adsorbent for adsorbing, purifying and enriching coalbed methane, a method for preparing the coal-based carbonaceous adsorbent, and a method for using the coal-based carbonaceous adsorbent to enrich coalbed methane.

[0008] The first aspect of the present invention provides a method for preparing a coal-based carbonaceous adsorbent for enriching coalbed methane, comprising:

[0009] 1) Mixing coal with a certain concentration of potassium hydroxide or sodium hydroxide solution, and then subjecting the mixture to a hydrothermal reaction at a temperature of 60°C-80°C. After the reaction is completed, the mixture is allowed to stand, cooled to room temperature, and pH is adjusted using dilute hydrochloric acid; the product is dried to obtain a precursor of a coal-based carbonaceous adsorbent;

[0010] 2) The precursor is transferred to a tube furnace and carbonized at a high temperature of 600° C. to 800° C. in an inert atmosphere. After the carbonization is completed, the precursor is cooled to room temperature, and the solid material is taken out, and the coal-based carbonaceous adsorbent is obtained after acid washing, filtering and drying.

[0011] Furthermore, in step 1), the coal includes lignite, long flame coal and weathered coal.

[0012] Furthermore, in step 1), the concentration of the certain concentration of potassium hydroxide or sodium hydroxide solution is 0.5-1 mol / L.

[0013] Furthermore, the liquid-solid ratio of the potassium hydroxide or sodium hydroxide solution to the coal is in the range of 20-30 mL / g.

[0014] Furthermore, in step 1), the pH is adjusted to 9-10.

[0015] A second aspect of the present invention provides a coal-based carbonaceous adsorbent, wherein the coal-based carbonaceous adsorbent is prepared by using the preparation method described in the first aspect.

[0016] The third aspect of the present invention provides a method for enriching coalbed methane, which is enriched by using the coal-based carbonaceous adsorbent as described in the second aspect and adopting an adsorption method.

[0017] Furthermore, the coal-based carbonaceous adsorbent is used to separate the CH4 / N2 mixed gas in the coalbed methane by an adsorption method, and the adsorption conditions are 0°C-30°C and the pressure is 0.1MPa-1MPa.

[0018] The present invention attempts to provide a coal-based carbonaceous adsorbent for adsorbing, purifying and enriching coalbed methane, a method for preparing the coal-based carbonaceous adsorbent, and a method for using the coal-based carbonaceous adsorbent to enrich coalbed methane.

[0019] Compared with existing adsorption materials and methods for preparing existing materials, the coal-based carbonaceous adsorbent provided by the present invention has the following advantages.

[0020] (1) The method of the present invention uses low-rank coal as a raw material to extract humic acid through an alkaline dissolution method, and uses it as a carbon material precursor to prepare a coal-based adsorbent. Compared with other preparation processes of coal-based carbon material adsorbents using potassium hydroxide for chemical activation, no chemical activator is required during the preparation process, and the product separation performance is excellent. Compared with existing adsorbent materials and preparation methods, the preparation method of the adsorbent material of the present invention also has the advantages of cheap and easy-to-obtain raw materials, simple preparation process, green and environmentally friendly preparation process, and high product yield.

[0021] (2) Compared with other adsorbents such as metal organic frameworks (MOFs) and molecular sieves, the coal-based carbonaceous adsorbent prepared by the method of the present invention has the advantages of a wide source of raw materials, developed product pores and high stability, and can broaden the utilization channels of low-rank coal while achieving methane enrichment, thereby improving the economic utilization benefits of low-rank coal and expanding the utilization channels.

[0022] (3) The coal-based carbonaceous adsorbent prepared by the method of the present invention requires a significantly lower amount of activation alkali than other similar carbon adsorbent materials, and the preparation process is more environmentally friendly. The product has higher adsorption selectivity and excellent adsorption selectivity performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a curve chart of BET characterization of the HAC-600 adsorbent material prepared in Example 1.

[0024] Figure 2 It is a curve chart of the adsorption of methane and nitrogen by the HAC-600 adsorption material prepared in Example 1 under the conditions of 298K and 100kPa.

[0025] Figure 3It is a curve chart of the adsorption of methane and nitrogen by the HAC-600 adsorption material prepared in Example 1 under the conditions of 273K and 100kPa.

[0026] Figure 4 It is a curve diagram of the adsorption selectivity of the HAC-600 adsorbent material prepared in Example 1 for CH4 / N2 mixed gas at 298K and 273K calculated based on the IAST theory. DETAILED DESCRIPTION

[0027] In order to provide a further understanding of the purpose, structure, features, and functions of the present invention, the following detailed description is given in conjunction with the embodiments.

[0028] The specific implementation of the technical solution of the present invention is further described below through specific examples.

[0029] [Example 1]

[0030] S1. Preparation of adsorption materials

[0031] Weigh 20g of lignite and disperse it in 400mL of 0.5mol / L KOH solution and stir for 30 minutes. Then transfer the mixture to a constant temperature water bath and hydrothermally react at 80℃ for 4 hours. Cool the mixture after the hydrothermal reaction, and then adjust its pH to 8-9 with 0.1mol / L dilute hydrochloric acid. After drying, the carbon material precursor is obtained. Use a tubular furnace in a nitrogen atmosphere to raise the target temperature to 600℃ at a rate of 5℃ / min and activate for 2h. After cooling to room temperature, the obtained carbon material is dispersed in 50mL of 1mol / L HCl solution, placed at 80℃ for 1h, and rinsed with deionized water until the pH value reaches neutral. After vacuum drying at 80℃ for 12h, the obtained carbonaceous adsorption material is named HAC-600.

[0032] S2. Structural characterization of adsorbent materials

[0033] About 100 mg of HAC-600 carbonaceous adsorption material was weighed and degassed at 150 °C for 8 h. The adsorption test was performed using a physical adsorption instrument Micromeritics tristarⅡ at 77 K using N2 as a gas probe to obtain its N2 adsorption curve (e.g. Figure 1 The analysis shows that the adsorption curve has a large hysteresis loop, indicating that the material contains a certain amount of mesopores and macropores, which is conducive to gas transmission. The specific surface area of ​​HAC-600 adsorption material is 621.88m 2 / g, and the total pore volume is 0.388cm 3 / g, of which the micropore volume (<2nm) is 552.24cm 3 / g, micropore volume (<0.8nm) is 0.234cm3 / g.

[0034] S3. Adsorption material product performance test

[0035] The physical adsorption instrument Micromeritics ASPA 2460 was used to perform static adsorption selectivity tests of CH4 and N2 at 273K and 298K under normal pressure. The test method is as follows: weigh about 100 mg of HAC-600 carbonaceous adsorption material, degas at 150°C for 8 hours, and use the physical adsorption instrument Micromeritics ASPA 2460 to test the gas adsorption amount at different equilibrium pressures, and obtain the adsorption isotherms at different temperatures (such as Figure 2 and Figure 3 Then the IAST model was used to calculate the static adsorption selectivity of CH4 / N2 of HAC-600 material at 273K and 298K. The calculation results are shown in Figure 4 .

[0036] Depend on Figure 4 It can be seen that at normal pressure and 298K, the CH4 adsorption capacity of HAC-600 is as high as 12.56 cm 3 / g, the CH4 / N2 selectivity of HAC-600 is as high as 6.92. Under normal pressure and 273K environment, the CH4 adsorption capacity is as high as 19.71cm 3 / g, the CH4 / N2 selectivity of HAC-600 is as high as 6.89, indicating that the coal-based carbonaceous adsorbent provided in this embodiment has a high adsorption capacity and excellent adsorption selectivity.

[0037] [Example 2]

[0038] Weigh 20g of lignite and disperse it in 400mL of 0.5mol / L KOH solution and stir for 30 minutes. Then transfer the mixture to a constant temperature water bath and hydrothermally react at 80℃ for 4 hours. Cool the mixture after the hydrothermal reaction, and then adjust its pH to 8-9 with 0.1mol / L dilute hydrochloric acid. After drying, the carbon material precursor is obtained. Use a tubular furnace in a nitrogen atmosphere to increase the temperature to 700℃ at a rate of 5℃ / min and activate for 2h. After cooling to room temperature, the obtained carbon material is dispersed in 50mL of 1mol / L HCl solution, placed at 80℃ for 1h, and rinsed with deionized water until the pH value reaches neutral. After vacuum drying at 80℃ for 12h, the carbonaceous adsorption material is obtained.

[0039] About 100 mg of carbonaceous adsorbent material was weighed, degassed at 150 °C for 8 h, and adsorbed using a physical adsorption instrument Micromeritics tristar II at 77 K using N2 as a gas probe to obtain its N2 adsorption curve. The specific surface area of ​​the adsorbent material was determined to be 742.97 m 2 / g, and the total pore volume is 0.408cm 3 / g, of which the micropore volume (<2nm) is 642.54cm 3 / g, micropore volume (<0.8nm) is 0.304cm 3 / g.

[0040] [Example 3]

[0041] Weigh 20g of long flame coal and disperse it in 400mL of 0.5mol / L KOH solution and stir for 30 minutes. Then transfer the mixture to a constant temperature water bath and hydrothermally react at 80℃ for 4 hours. Cool the mixture after the hydrothermal reaction, and then adjust its pH to 8-9 with 0.1mol / L dilute hydrochloric acid. After drying, the carbon material precursor is obtained. Use a tubular furnace in a nitrogen atmosphere to increase the temperature to 800℃ at a rate of 5℃ / min and activate for 2h. After cooling to room temperature, the obtained carbon material is dispersed in 50mL of 1mol / L HCl solution, placed at 80℃ for 1h, and rinsed with deionized water until the pH value reaches neutral. After vacuum drying at 80℃ for 12h, the carbonaceous adsorption material is obtained.

[0042] About 100 mg of carbonaceous adsorbent material was weighed, degassed at 150 °C for 8 h, and adsorbed using a physical adsorption instrument Micromeritics tristar II at 77 K using N2 as a gas probe to obtain its N2 adsorption curve. The specific surface area of ​​the adsorbent material was determined to be 880.33 m 2 / g, and the total pore volume is 0.432cm 3 / g, of which the micropore volume (<2nm) is 478.36cm 3 / g, micropore volume (<0.8nm) is 0.240cm 3 / g.

[0043] [Example 4]

[0044] Weigh 20g of lignite and disperse it in 400mL of 0.5mol / L NaOH solution and stir for 30 minutes. Then transfer the mixture to a constant temperature water bath and hydrothermally react at 80℃ for 4 hours. Cool the mixture after the hydrothermal reaction, and then adjust its pH to 8-9 with 0.1mol / L dilute hydrochloric acid. After drying, the carbon material precursor is obtained. Use a tubular furnace in a nitrogen atmosphere to increase the temperature to 600℃ at a rate of 5℃ / min and activate for 2h. After cooling to room temperature, the obtained carbon material is dispersed in 50mL of 1mol / LHCl solution, placed at 80℃ for 1h, and rinsed with deionized water until the pH value reaches neutral. After vacuum drying at 80℃ for 12h, the carbonaceous adsorption material is obtained.

[0045] About 100 mg of carbonaceous adsorbent material was weighed, degassed at 150 °C for 8 h, and adsorbed using a physical adsorption instrument Micromeritics tristar II at 77 K using N2 as a gas probe to obtain its N2 adsorption curve. The specific surface area of ​​the adsorbent material was determined to be 621.88 m 2 / g, and the total pore volume is 0.388cm 3 / g, of which the micropore volume (<2nm) is 552.24cm 3 / g, micropore volume (<0.8nm) is 0.234cm 3 / g.

[0046] [Example 5]

[0047] Weigh 20g of weathered coal and disperse it in 400mL of 0.5mol / L KOH solution and stir for 30 minutes. Then transfer the mixture to a constant temperature water bath and hydrothermally react at 80℃ for 4 hours. Cool the mixture after the hydrothermal reaction, and then adjust its pH to 8-9 with 0.1mol / L dilute hydrochloric acid. After drying, the carbon material precursor is obtained. Use a tubular furnace in a nitrogen atmosphere to increase the temperature to 600℃ at a rate of 5℃ / min and activate for 2h. After cooling to room temperature, the obtained carbon material is dispersed in 50mL of 1mol / L HCl solution, placed at 80℃ for 1h, and rinsed with deionized water until the pH value reaches neutral. After vacuum drying at 80℃ for 12h, the carbonaceous adsorption material is obtained.

[0048] About 100 mg of carbonaceous adsorbent material was weighed, degassed at 150 °C for 8 h, and adsorbed using a physical adsorption instrument Micromeritics tristar II at 77 K using N2 as a gas probe to obtain its N2 adsorption curve. The specific surface area of ​​the adsorbent material was determined to be 687.40 m 2 / g, and the total pore volume is 0.336cm 3 / g, of which the micropore volume (<2nm) is 480.08cm 3 / g, micropore volume (<0.8nm) is 0.226cm 3 / g.

[0049] [Example 6]

[0050] Weigh 20g of weathered coal and disperse it in 400mL of 0.5mol / L NaOH solution and stir for 30 minutes. Then transfer the mixture to a constant temperature water bath and hydrothermally react at 80℃ for 4 hours. Cool the mixture after the hydrothermal reaction, and then adjust its pH to 8-9 with 0.1mol / L dilute hydrochloric acid. After drying, the carbon material precursor is obtained. Use a tubular furnace in a nitrogen atmosphere to increase the temperature to 600℃ at a rate of 5℃ / min and activate for 2h. After cooling to room temperature, the obtained carbon material is dispersed in 50mL of 1mol / L HCl solution, placed at 80℃ for 1h, and rinsed with deionized water until the pH value reaches neutral. After vacuum drying at 80℃ for 12h, the carbonaceous adsorption material is obtained.

[0051] About 100 mg of carbonaceous adsorbent material was weighed, degassed at 150 °C for 8 h, and adsorbed using a physical adsorption instrument Micromeritics tristar II at 77 K using N2 as a gas probe to obtain its N2 adsorption curve. The specific surface area of ​​the adsorbent material was determined to be 603.49 m 2 / g, and the total pore volume is 0.363cm 3 / g, of which the micropore volume (<2nm) is 457.69cm 3 / g, micropore volume (<0.8nm) is 0.219cm 3 / g.

[0052] The adsorbent materials of Examples 1-6 were subjected to static adsorption tests of methane and nitrogen at 298K and normal pressure, respectively. The IAST (Ideal Adsorbed Solution Theory) model was used to calculate the static adsorption selectivity of CH4 / N2 of the adsorbent materials of Examples 1-6 at 298K and normal pressure. The experimental data obtained are as follows:

[0053]

[0054] It can be seen from the above table that the adsorption materials of Examples 1-6 have strong adsorption capacity for methane and good adsorption selectivity.

[0055] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

[0056] In the description of the present invention, it is necessary to understand that the terms “longitudinal”, “lateral”, “length”, “width”, “thickness”, “up”, “down”, “front”, “back”, “left”, “right”, “vertical”, “horizontal”, “top”, “bottom”, “inside” and “outside” orientations or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention.

[0057] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. A method for preparing a coal-based carbonaceous adsorbent for enriching coalbed methane, characterized in that: include: 1) Mixing coal with a certain concentration of potassium hydroxide or sodium hydroxide solution, and then subjecting the mixture to a hydrothermal reaction at a temperature of 60°C-80°C. After the reaction is completed, the mixture is allowed to stand, cooled to room temperature, and pH is adjusted using dilute hydrochloric acid; the product is dried to obtain a precursor of a coal-based carbonaceous adsorbent; 2) The precursor is transferred to a tube furnace and carbonized at a high temperature of 600° C. to 800° C. in an inert atmosphere. After the carbonization is completed, the precursor is cooled to room temperature, and the solid material is taken out, and the coal-based carbonaceous adsorbent is obtained after acid washing, filtering and drying.

2. The method for preparing a coal-based carbonaceous adsorbent for enriching coalbed methane according to claim 1, characterized in that: In step 1), the coal includes lignite, long flame coal and weathered coal.

3. The method for preparing a coal-based carbonaceous adsorbent for enriching coalbed methane according to claim 1, characterized in that: In step 1), the concentration of the potassium hydroxide or sodium hydroxide solution of a certain concentration is 0.5-1 mol / L.

4. The method for preparing a coal-based carbonaceous adsorbent for enriching coalbed methane according to claim 1, characterized in that: The liquid-solid ratio of potassium hydroxide or sodium hydroxide solution to coal is in the range of 20-30 mL / g.

5. The method for preparing a coal-based carbonaceous adsorbent for enriching coalbed methane according to claim 1, characterized in that: In step 1), the pH is adjusted to 9-10.

6. A coal-based carbonaceous adsorbent, characterized in that: The coal-based carbonaceous adsorbent is prepared by using the preparation method according to any one of claims 1 to 5.

7. A method for enriching coalbed methane, characterized in that: Coalbed methane is enriched by using the coal-based carbonaceous adsorbent as claimed in claim 6 using an adsorption method.

8. The method for enriching coalbed methane according to claim 7, characterized in that: The coal-based carbonaceous adsorbent is used to separate the CH4 / N2 mixed gas in coalbed methane by an adsorption method, and the adsorption conditions are 0°C-30°C and the pressure is 0.1MPa-1MPa.

Citation Information

Patent Citations

  • Porous activated carbon material for adsorbing carbon dioxide and preparation method thereof

    CN112830490A

  • Ultramicroporous carbon material prepared from chitosan, preparation method of ultramicroporous carbon material and method for high-selectivity separation of small molecular hydrocarbon

    CN116116389A